Efektivitas Repelan Losion Minyak Atsiri Kulit Jeruk Bali (Citrus maxima (Burm.) Merr.) terhadap Aedes aegypti - Nurul Hidayah; Hasrida Mustafa; Murni Murni; Intan Tolistiawaty (Balai Penelitian dan Pengembangan Kesehatan Banjarnegara Badan Litbangkes Kemenkes RI, 2018)
The use of chemicals as the main ingredient for the manufacture of anti mosquito products can be hazardous to health, so bio-insecticides derived from plants such as grapefruit (C. maxima (Burm.) Merr.) is needed as alternatif. Balinese Orange (​C. maxima (Burm.) Merr.) peel has an essential oil which can be utilized as an environmentally friendly insect repellent. The aim of this study was to know repellent test of essential oil of Balinese orange peel in lotion form. Design of this study is quasi-experiment with five different treatments. Substance concentration for the repellent test were 10%, 20%, 40%, 60%, and 80% in lotion form. The repellent test referred to Ministry of Agriculture Pesticide Efficacy Test Standard guidelines. The result of the experiment showed lotion from C. maxima (Burm.) Merr. essential oil has a repellent potency between 36%-96%. Maximum protection was found at the beginning of the application and was declining towards the end of observation. The lotion of C. maxima (Burm.) Merr. essential oil has its highest repellent potency at 40% concentration during hour-0 and hour-1. The repellent potency of C. maxima (Burm.) Merr. essential oil has a high potential as an insect repellent, however, further research is needed for finding alternative methods of extraction to obtain higher essence, creating the repellent in other forms or combining with substances from other essential oil. ABSTRAKPenggunaan bahan kimia sebagai bahan utama pembuatan produk anti nyamuk dapat berbahaya bagi kesehatan, sehingga perlu insektisida hayati yang berasal dari tumbuhan, seperti jeruk bali (Citrus maxima (Burm.) Merr.). Kulit jeruk bali (C. maxima (Burm.) Merr.) mengandung minyak atsiri yang dapat digunakan sebagai repelan yang ramah lingkungan. Penelitian ini bertujuan untuk mengetahui efektifitas repelan/daya tolak minyak atsiri kulit jeruk bali (C. maxima (Burm.) Merr.) dalam sediaan losion. Jenis penelitian adalah eksperimental semu dengan menggunakan konsentrasi minyak atsiri ekstrak kulit jeruk bali (C. maxima (Burm.) Merr.) 10%, 20%, 40%, 60%, dan 80% dalam sediaan losion. Pengujian mengacu pada petunjuk teknis Standar Pengujian Efikasi Pestisida Kementerian Pertanian. Hasil penelitian menunjukkan bahwa losion minyak atsiri kulit jeruk bali (C. maxima (Burm.) Merr.) memiliki daya tolak antara 36-96%. Daya tolak tertinggi pada konsentrasi 40% dengan waktu paling efektif dari jam ke-0 sampai jam ke-1. Daya repelan dari minyak atsiri kulit jeruk bali (C. maxima (Burm.) Merr.) sangat berpotensi namun perlu dikembangkan metode ekstraksi untuk mendapatkan konsentrat yang lebih tinggi, pembuatan sediaan dalam bentuk lain, atau mengkombinasikan dengan senyawa dari minyak atsiri yang lain.